Study on Aerodynamic Performance of Propeller with Tip Winglet - Yang, Yueqi (International Journal of Mechanical and Electrical Engineering, 2024)
Based on the Reynolds-averaged Navier-Stokes governing equations and the unstructured grid rotating/stationary sliding surface technology, this paper studies the aerodynamic layout and efficiency enhancement mechanism of the near-space propeller blade tip winglet configuration. First, the feasibility of the configuration is verified by comparing and analyzing different lift propeller layout schemes. Secondly, the aerodynamic layout design of the blade tip winglet propeller is studied by changing the winglet inclination angle and length parameter indicators. Finally, the ANSYS simulation analysis is used to calculate the influence of the winglet design on the propeller velocity vector distribution, blade pressure and propeller aerodynamic efficiency, and the performance influence law of the basic parameters is preliminarily established, and the overall design scheme of the new blade tip winglet propeller design is completed. The study shows that the blade tip winglet propeller layout is a reasonable and feasible technical approach to improve the aerodynamic efficiency in the near-space working environment, and it has a certain reference role in the development of new configuration propeller aircraft.